2000
DOI: 10.1260/0263092001492895
|View full text |Cite
|
Sign up to set email alerts
|

Unpleasantness and Acceptable Limits of Low Frequency Sound

Abstract: SUMMARY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
32
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 3 publications
7
32
1
Order By: Relevance
“…This, along with other related work implies that noise at low frequencies is considered more annoying by individuals (Broner, 1978;Berglund et al, 1996;Pawlaczyk-Luszczynska, 2010). Moreover, related research has also found that low frequency noise has a greater degree of 'unpleasantness' than noise in the A-weighted frequency bands (Inukai et al, 2000;Nakamura and Inukai, 1998). Exposure to low frequency noise also causes sleep disturbance (Leventhall, 2003) and its associated secondary effects with the WHO (Berglund et al, 1999) noting that it 'can disturb rest and sleep even at low sound levels'.…”
Section: Introductionsupporting
confidence: 56%
“…This, along with other related work implies that noise at low frequencies is considered more annoying by individuals (Broner, 1978;Berglund et al, 1996;Pawlaczyk-Luszczynska, 2010). Moreover, related research has also found that low frequency noise has a greater degree of 'unpleasantness' than noise in the A-weighted frequency bands (Inukai et al, 2000;Nakamura and Inukai, 1998). Exposure to low frequency noise also causes sleep disturbance (Leventhall, 2003) and its associated secondary effects with the WHO (Berglund et al, 1999) noting that it 'can disturb rest and sleep even at low sound levels'.…”
Section: Introductionsupporting
confidence: 56%
“…These adverse psychological effects can be induced even by low-level low-frequency noise in living environments 8,9) and they are expected to be more prevalent in working environments where high-level low-frequency noises are generated [10][11][12] . Inukai et al 13) reported that the slopes of the equalunpleasantness level contours are very similar to those of the equal-loudness level contours. This finding indicates that hearing sensation plays an important role in perceiving unpleasantness or annoyance of persons exposed to lowfrequency noise, despite the low audibility of the noise.…”
Section: Introductionmentioning
confidence: 82%
“…There is of course, a wide range of possible stimuli, which experimenters have chosen according to their experience of what is required. (Adam, 1999;Andresen and Moller,1984;Broner and Leventhall, 1978b;Broner and Leventhall, 1984;Broner and Leventhall,1985;Goldstein,1994;Goldstein and Kjellberg, 1985;Inukai et al, 2000;Kjellberg and Goldstein, 1985;Kjellberg et al, 1984;Moller,1987;Nakamura and Inukai,1998;Persson-Waye,1985;Persson and Bjorkman,1988;Poulsen, 2002;Poulsen, 2003a;Poulsen, 2003b;Poulsen and Mortensen, 2002). Some of the laboratory studies have used recordings of real noises as stimuli, whilst others have worked with recordings of the actual noises as experienced by subjects in their own work places or homes.…”
Section: Annoyance Measurementsmentioning
confidence: 99%